Cadmium fume inhalation and emphysema. - Davison, A; Fayers, P; Taylor, A; Venables, K; Darbyshire, J; Pickering, C; Chettle, DR; Franklin, D; Guthrie, C; Scott, M (1988)
Lung function and chest radiographs of 101 men who had worked for 1 or more years manufacturing copper-cadmium alloy were compared with those of a referent group matched for age, sex, and employment status. Cigarette consumption was similar in the two groups. The cadmium workers had an excess of abnormalities of lung function and of radiographic changes consistent with emphysema. Classification of the cadmium workers by exposure categories based on either estimated cumulative cadmium exposure or liver cadmium measured by neutron activation analysis showed that abnormalities of lung function were greatest in those with the highest cumulative cadmium exposure or liver cadmium. The difference in the transfer coefficient (KCO) between cadmium workers and referents increased linearly with increasing cumulative exposure without evidence for a threshold. The estimated mean decrement in KCO for a cadmium worker employed 5 or more years with a cumulative exposure of 2000 yr.microgram.m-3 (exposure to the current UK control limit of 50 micrograms.m-3 for a working lifetime of 40 yr) lies between 0.05 and 0.3 mmol.min-1.kPa-1.l-1 (95% confidence interval). This decrement is consistent with the functional and radiological changes of emphysema observed in this group of workers.